Influence of Temperature on the Growth of Vertically Aligned ZnO Nanowires in Wet Oxygen Environment - Basma ElZein; Numan Salah; Ahmad S. Barham; Ali Elrashidi; Mohammed Al Khatab; Ghassan Jabbour (Crystals, 2023)
The nanowires (NWs) of zinc oxide (ZnO) are developed effectively on an n-type silicon substrate through a seed zinc (Zn) layer by a wet oxidation technique. The growth is performed at different temperatures, 650, 750, and 850 °C, in a wet and rich oxygen environment under a flow of oxygen in the presence of water vapor at atmospheric pressure with a heating rate of 100 °C in 30 min. At 415 °C, the oxygen gas is introduced for the oxidation process. The Zn seed layer is deposited by the thermal evaporation technique. The structural, morphological, and optical properties are investigated. The temperature effect on NWs of ZnO growth intensity and their direction are explored. The nanowires are grown vertically oriented at a temperature of T = 750 °C. The ultraviolet (UV) analysis has been exposed in the visible region ranging from 10 nm to 700 nm at UV to visible intensity ratio of 2.22. In addition, X-ray diffraction analysis (XRD) is employed to research the structural properties of NWs of ZnO, and the characterization is verified by a scanning electron microscope (SEM) to investigate the morphology.